Time Series Momentum in Sector Based ETFs: Does a Momentum Effect Exist? - Cole, Corey D.; Schneider , Robert; Hemley, David; Nations , Morgen (Journal of Accounting and Finance, 2021)
The population utilized for this study was exchanged-traded-funds (ETFs) offered by The Vanguard Group® for years 2006 through 2018. The purpose of this quantitative study was to test for a momentum effect in eight of the S&P 500 sectors, and then to introduce risk and speculation as additional independent variables. The level of the presence of momentum was measured within each sector using a regression analysis at the 99% confidence level. This study showed no statistically significant presence of the momentum effect in all eight sectors, with the addition of risk positively affecting two of the eight sectors, and the addition of speculation affecting all eight sectors negatively. These findings do not support the viability of a momentum-based investment strategy. In addition, both risk and speculation should always be closely monitored in any portfolio.